Schizochytrium limacinum Supplementation in a Low Fish-Meal Diet Improved Immune Response and Intestinal Health of Juvenile Penaeus monodon - Xie, Shiwei; Wei, Dan; Tan, Beiping; Liu, Yongjian; Tian, Lixia; Niu, Jin (Frontiers in Physiology, 2020)
The aim of present experiment was to evaluate the effects of Schizochytrium limacinum sup-plementation on immune response, and gut microbiota and health of Penaeus monodon fed a low FM diet. A diet containing 25% FM was used as a control (Diet A), and three other diets were for-mulated to contain 15% FM and supplemented with 0, 0.75%, 1.5% S. limacinum (Diet B, C and D, respectively). The experiment was done in quadruplicates (30 shrimp per replicate, average weight 1.01 ± 0.01g) and the shrimps were fed the test diets to apparent satiation three times daily for eight weeks. Shrimp fed diet B and D showed lower weight gain than those fed diet A. Supplementation of 0.75% S. limacinum enhanced expression of anti-oxidative genes (superoxide dismutase and catalase) and immune response related genes in hepatopancreas, but could not affect the gene expression of immune deficiency (IMD) in hepatopancreas and Tube in intestine. Low FM diet induced endoplasmic reticulum swelling of the intestinal epithelial cells, which was alleviated by S. limacinum supplementation. UPLC-QTOF-MS was employed to analyze the changes of hemolymph metabolomics, and 49 significantly different metabolites were identified, lysoPCs, deoxyinosine, inosine and highly unsaturated fatty acids were lower in fish fed low FM diets. Intestinal microbial diversity was lower in shrimp fed Diet B than those fed the control diet. Dietary supplementation of 0.75% S. limacinum increased intestinal microbial diversity of shrimp and decreased the ratio of pathogenic bacterium (Thalassotalea and Tenacibaculum). These results indicated that supplementing S. limacinum in a low FM diet improves growth performance, immune response and intestinal health of P. monodon. The optimum inclusion level of seems to be 0.75% of diet.